Formulação de inovações educacionais: desafios de gestão em uma universidade federal em tempos da pandemia Covid-19 - Cruz, Layra Natividade da (Brasil, 2025)
The general objective of the study was to analyze the educational challenges and innovations encountered by managers by a federal university in the face of the covid-19 emergency scenario. There was an emergency to formulate an adaptation, through a transition from face-to-face teaching to remote teaching as an alternative to serve the academic community. The research has a qualitative approach through a descriptive investigation. The data collection technique adopted consisted of semi-structured interviews, based on a previously prepared script. The study involved the participation of eight university managers, from the Bachelor's degree in Administration, Economics and Accounting. Content analysis was the technique used, based on the transcripts of the interviews. From them, thematic categories were formed, organized according to the experiences and perspectives of the interviewees. The results obtained were the challenges related to the impact of the suspension of activities on the functions of managers, slowness in decision-making, the process of convincing to adapt to remote teaching and the low-quality internet service. The changes at the university were the adoption of emergency remote teaching, teacher training, the use of information and communication technologies ICTs, and changes in administrative activities. The educational innovation most mentioned in the interviews refers to digital inclusion with the loan of technological equipment and the offer of chips with internet for students.